Peripheral IgE Repertoires of Healthy Donors Carry Moderate Mutation Loads and Do Not Overlap With Other Isotypes - Koning, Marvyn T.; Trollmann, Ignis J. M.; van Bergen, Cornelis A. M.; Saravia, Diego Alvarez; Navarrete Signorile, Marcelo Alejandro; Kielbasa, Szymon M.; Veelken, Hendrik (My University, 2019)
IgE-mediated allergic disease represents an increasing health problem. Although numerous studies have investigated IgE sequences in allergic patients, little information is available on the healthy IgE repertoire. IgM, IgG, IgA, and IgE transcripts from peripheral blood B cells of five healthy, non-atopic individuals were amplified by unbiased, template-switching, isotype-specific PCR. Complete VDJ regions were sequenced to near-exhaustion on the PacBio platform. Sequences were analyzed for clonal relationships, degree of somatic hypermutation, IGHV gene usage, evidence of antigenic selection, and N-linked glycosylation motifs. IgE repertoires appeared to be highly oligoclonal with preferential usage of certain IGHV genes compared to the other isotypes. IgE sequences carried more somatic mutations than IgM, yet fewer than IgG and IgA. Many IgE sequences contained N-linked glycosylation motifs. IgE sequences had no clonal relationship with the other isotypes. The IgE repertoire in healthy individuals is derived from relatively few clonal expansions without apparent relations to immune reactions that give rise to IgG or IgA. The mutational burden of normal IgE suggests an origin through direct class-switching from the IgM repertoire with little evidence of antigenic drive, and hence presumably low affinity for specific antigens. These findings are compatible with a primary function of the healthy IgE repertoire to occupy Fc epsilon receptors for competitive protection against mast cell degranulation induced by allergen-specific, high-affinity IgE. This background knowledge may help to elucidate pathogenic mechanisms in allergic disease and to design improved desensitization strategies.
Keywords: affinity maturation; allergy; b-cell receptor; class switching; ige